Development and evaluation of a novel caregiver-report tool to assess barriers to physical healthcare for people on the autism spectrum. (November 2020) - Walsh, C.; Lydon, S.; Hehir, A.; O'Connor, P.
Highlights: A novel caregiver-report Barriers to Healthcare tool for autistic individuals was developed and evaluated. Results suggest that barriers to healthcare occur at the patient, healthcare-provider and systems levels. Autism severity, anxiety, general adjustment problems, age, and having unmet needs significantly predicted barriers endorsed. This tool may guide the development and evaluation of initiatives to reduce healthcare barriers for autistic individuals; Abstract: Introduction: People on the autism spectrum often experience poorer health than the general population despite higher engagement with the health services. This suggests a disparity in the accessibility of appropriate healthcare for autistic individuals. To improve access, barriers the autism community experience in healthcare first need to be identified. This paper aimed to: 1) develop and evaluate a caregiver-report tool; 2) identify barriers to physical healthcare for autistic individuals; and 3) identify potential contributing factors. Methods: A previously established taxonomy of barriers to healthcare for autistic individuals informed the development of the tool; this was then distributed to caregivers of autistic adults and children. Exploratory factor analysis (EFA) assessed validity and reliability of the tool. Multiple Regressions were performed to identify predictors of barriers. Results: In total, caregivers of 194 autistic children or adults participated in the study. The EFA produced four factors: 1) patient-level barriers; 2) healthcare provider-level (HCP) barriers; 3) healthcare system-level barriers; and 4) barriers related to managing healthcare. The greatest barriers included difficulties with identifying/reporting symptoms (endorsed by 62.4% of participants); difficulties handling the waiting area (60.3% of participants); and a lack of HCP knowledge regarding autism (52.1% of participants). Autism severity, general adjustment problems, anxiety, age and having unmet needs predicted the frequency and/or severity of barriers. Conclusions: A tool that allows assessment of patient-, HCP-, and system-level barriers to healthcare was developed and evaluated. Patient-level barriers appear to occur frequently and pose substantial challenges. This tool will help identify areas most in need of intervention and support intervention evaluation.